PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, LIKUIDITAS DAN STRUKTUR AKTIFA TERHADAP STRUKTUR MODAL PERUSAHAAN MANUFAKTUR GO PUBLIK (Studi Sektor Kosmetik Dan Keperluan Rumah Tangga) - Shelly Armelia; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The purpose of this study was to investigate the firm size, profitability, liquidity and asset structure to the capital manufacturing companies. This study focused on Cosmetic and Household use sector companies listed in Bursa Efek Indonesia for period 2010-2015. The data used in this research is secondary data, financial highlights (annual report) and performance summary. This study used purposive sampling method in order to collect the sample. Analysis of data using multiple linear regression analysis with SPSS 19.The result of this research indicates that firm size, profitability, liquidity and asset structure simultaneously significantly influence to capital structure. The values that have been adjusted coefficient of determination (adjusted R-square) for 87,6% can be concluded that factors, while the remaining amount of 12,4% influenced by other variables that are not included in this study, for example earning stability, operating leverage, growth opportunity and tax.Keywords : Capital Structure, Firm Size, Profitability, Liquidity and Asset Structure